Numerical study of magnetohydrodynamic free convective heat transfer flow along a vertical flat plate with temperature dependent thermal conductivity (Journal of Naval Architecture and Marine Engineering, 2010)
The present numerical work describes the effect of the magnetohydrodynamic (MHD) free convective heat transfer flow along a vertical flat plate with temperature dependent thermal conductivity and heat conduction. The governing equations reduce to local non-similarity boundary layer equations using suitable transformation have been integrated by employing an implicit finite difference method together with the Keller box technique. Comparison with previously published work is performed and excellent agreement is observed. Profiles of the dimensionless velocity and temperature distributions as well as the local skin friction coefficient and surface temperature distribution are shown graphically for various values of the magnetic parameter M, thermal conductivity variation parameter g and Prandtl number Pr.Keywords: Implicit finite difference method, free convection flow, vertical flow, vertical flat plate, temperature dependent thermal conductivityDOI: 10.3329/jname.v6i1.2654Journal of Naval Architecture and Marine Engineering Vol.6(1) 2009 16-29